Does Experience Lead People to Buy? The Formation of Brand Loyalty Using the Theory of Love on Older Consumers - Bertina Sjabadhyni; Martina Dwi Mustika; Kinanti Alvani Pane; Deepraj Kaur; Alvin Eryandra (Humaniora, 2019)
This research investigated factors that influence the positive brand experiences of older consumers that lead them to be loyal to the product. Data were collected using a paper-based survey, and 362 older consumers participated in the research. Using path analysis, the results suggested that the relationship between brand experience and brand loyalty was stronger when the experience of older consumers predicted their loyalty through affectivity and trust. This research provided evidence that the consumer and brand relationship could be explained using the triangular theory of love and the theory of planned behavior. It can be concluded that the affection and trust of older consumers are essential. Thus, their experience of the product leadsto loyalty.